ANO9 regulates PD‐L2 expression and binding ability to PD‐1 in gastric cancer. Issue 3 (22nd January 2021) - Katsurahara, Keita; Shiozaki, Atsushi; Kosuga, Toshiyuki; Shimizu, Hiroki; Kudou, Michihiro; Arita, Tomohiro; Konishi, Hirotaka; Komatsu, Shuhei; Kubota, Takeshi; Fujiwara, Hitoshi; Okamoto, Kazuma; Kishimoto, Mitsuo; et al.
Abstract: The function of ANO9 in gastrointestinal cancer remains unclear. We investigated the biological behaviors and clinical prognostic values of ANO9 in gastric cancer (GC). Knockdown experiments were performed on human GC cell lines using ANO9 siRNA. Eighty‐four primary tissue samples from patients with advanced GC were examined immunohistochemically (IHC). Knockdown of ANO9 reduced the progression of cancer cells in MKN7 and MKN74 cells. A microarray analysis revealed that ANO9 regulated PD‐L2 via interferon (IFN)‐related genes. We confirmed using flow cytometry that the depletion of ANO9 reduced the binding ability to PD‐1 by downregulating the expression of PD‐L2 in MKN7 and MKN74 cells. IHC revealed a correlation between the expression of ANO9 and PD‐L2 and also that the strong expression of ANO9 was an independent poor prognostic factor in patients with advanced GC. The present results indicate that ANO9 regulates PD‐L2 and binding ability to PD‐1 via IFN‐related genes in GC. Therefore, ANO9 has potential as a biomarker and target of immune checkpoint blockage (ICB) for GC. Abstract : The depletion of ANO9 reduced the binding ability to PD‐1 by downregulating the expression of PD‐L2 in GC cells. This is the first report to clarify the mechanism of ANO9 regulating the immune escape of cancer cells via PD‐L2.